STUDENTS’ PERCEPTION OF ONLINE LEARNING TO ENHANCE THEIR READING COMPREHENSION SKILL TO THE ELEVENTH GRADE STUDENTS AT SMA TRISAKTI BATURAJA - Herni Septa Sari; Neti Lastri; Nopa Yusnilita (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2021)
This study analyzed students’ perception of online learning to enchance their reading comprehension skill. This study used the descriptive qualitative. The population of this research was students of Eleventh Grade Studens of SMA Trisakti Baturaja. The researcher took all of the sample by applying total sampling. The data was collected through the questionnaire. It consist of 10 statements. Then, the researcher used five percentage for analyzing the data. The result of this research were many students argued that they were disagree of online learning to enchance their reading comprehension skill. The data were in low criteria (61,46). It means that the students’ response toward the use of Online Learning to enchance their reading skill is not an effective tool for their learning.